History of Jammu - "Dewan, Parvez" (New Delhi, 2008)
In this first-of-its kind three-volume set on Jammu, Kashmir and Ladakh, one on each region, Parvez Dewan has tried to bring alive the past of the fabled land that has been the arena of his adult life.
Keywords: History-Kashmir